ANALYSIS OF AGRICULTURAL SECTOR DEVELOPMENT IN CENTRAL ASIA - Zhurynov G.M.; Abylkasym A.B.; Orazova B.B.; Karsakova G.P.; Taskulova G.M. (Academic Journal of Physical and Chemical Sciences, 2020)
Central Asia is one of the fastest growing regions of the world, with great potential for further development. All countries in the region are landlocked, some have valuable natural reserves of gas, oil and gold, and all countries have valuable human potential inherited from the Soviet era. Central Asia is also an important agricultural region, where the population has been growing grain and cotton, fruits and vegetables, animal feed and other essential foodstuffs from century to century. Agricultural production and processing, as well as related services, are an important source of income in many countries of Central Asia (20–25% of GDP in Kyrgyzstan, Tajikistan, and Uzbekistan). About two thirds of the region’s population live in rural areas. Meanwhile, various pests and diseases threaten agricultural productivity in the region, which causes significant harm to the economies of the countries. Agriculture in Central Asia faces many challenges, including fragmented production, poor productivity, underdeveloped markets, weak institutional structures, and a lack of public resources to support agriculture. In this situation, trade reforms, and corresponding changes in agricultural and trade policies, can play an important role in determining the direction of agricultural development. Due to the intensive participation of Central Asian countries in international trade through membership in the WTO, the Shanghai Cooperation Organization or the Eurasian Economic Union, the issues of harmonizing domestic policies and programs with these processes are becoming more and more relevant. States are faced with the task of ensuring that changes in trade policies are consistent with country development priorities. Thus, a clear understanding of trade rules and their implications for agriculture and food security is becoming a critical factor in strategic decision making.